Bom Intento em cena: memórias de um teatro ribeirinho e da floresta em Bujaru-PA (1980-2020) - CRUZ, Silvana da Silva (2023)
This Course Conclusion Paper presents itself as a study on the theatrical history in the city of Bujaru / PA, with the intention of unveiling memories, narratives and documents from the Cia de Teatro Bom Intento. The theoretical-methodological path was based on the studies of memory by Bosi (1994) and history for the promotion of reflections on scenic practices in the Amazon of Pará with Salles (1994) and Bezerra (2013). Oral history, based on Freitas (2001), presents itself as a methodological view of the research. For the survey of documentary sources that guarantee this critical-reflective writing, we work with listening to characters involved with the theater scene in question, in addition to being carriers of social, individual and collective memories of the municipality of Bujaru-PA. As a result of this process, we have: a) the historical narrative construction of the Cia de Teatro Bom Intento, the first reason that drove this research. b) The memories of this theatrical group allowed to enter the cultural memories of the municipality, the places, as people and the theatrical works that emerge from stages in the forest and on the banks of the rivers; c) a record of a memorial journey with the theater, showing works and influences that contribute to the process of my construction and growth as an active and black body in art.